Answer:B
f(x)-g(x) =(f -g)(x)= 3^x - 2x + 14
Explanation:
If f(x) = 3^x + 10 and g(x) = 2x-4
Find (f-g)(x)
This simply means or implies that
f(x)-g(x)
Factorizing (x) as the common factor
(x)(f-g) = (f-g)(x). They mean the same thing and can be used interchangeably.
So (f-g)(x) = f(x)-g(x)
[f(x) = 3^x + 10] - [g(x) = 2x-4]
= 3^x + 10 - (2x-4)
= 3^x + 10 - 2x+4
= collect like terms ( terms containing x together and the constants together)
3^x - 2x +4 + 10
= 3^x - 2x + 14
So the final answer is B
= 3^x - 2x + 14